Peace of Heart Perspective of Surah Al-Insyirah: Study of Tafsir Maudu'i - Nadea Siti Sa’adah; Siti Chodijah (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the calmness of the heart in the perspective of Al-Insyirah's letter on the study of maudui (thematic) interpretation. The research methodology used is a qualitative model through literature study, which is interpreted to produce knowledge. The results and discussion of this research are studies of Al-Insyirah’s letter in dissecting calmness of heart and spaciousness of the chest and the themes contained in it using the Maududi (thematic) interpretation method. So as to produce conclusions including calmness of heart, peace of mind, and spaciousness of the chest which will be obtained by each individual if he is able to endure, be patient, and trustworthy in living it. As in Al-Insyirah’s letter verses 1 to 8 which describe various aspects, namely spaciousness, lightness and calmness of heart, ease after difficulty, doing other work after completing one job, and making intentions and hopes only focused on Allah SWT